2021
DOI: 10.1038/s41586-021-04198-4
|View full text |Cite
|
Sign up to set email alerts
|

Unrepresentative big surveys significantly overestimated US vaccine uptake

Abstract: Surveys are a crucial tool for understanding public opinion and behaviour, and their accuracy depends on maintaining statistical representativeness of their target populations by minimizing biases from all sources. Increasing data size shrinks confidence intervals but magnifies the effect of survey bias: an instance of the Big Data Paradox 1 . Here we demonstrate this paradox in estimates of first-dose COVID-19 vaccine uptake in US adults from 9 January to 19 May 2021 from two large … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
185
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(191 citation statements)
references
References 28 publications
6
185
0
Order By: Relevance
“…Step 4: Bias adjustment: Since both fixed-and random-effects models were affected by the presence of very large datasets (albeit to a different extent), the question arises whether there is a possibility of adjusting for this large study bias. In Bradley et al (2021), the error could be directly deduced due to the nature of the survey data. This is however not easily possible in the context of meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Step 4: Bias adjustment: Since both fixed-and random-effects models were affected by the presence of very large datasets (albeit to a different extent), the question arises whether there is a possibility of adjusting for this large study bias. In Bradley et al (2021), the error could be directly deduced due to the nature of the survey data. This is however not easily possible in the context of meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the collection of extremely large datasets comes at the cost of data quality (Meng, 2018). A recent study has demonstrated that the effective sample size in large surveys can diminish by more than 99.99% if systematic bias is accounted for (Bradley et al, 2021). Since meta-analyses are typically based on inferential statistics and, even in random-effects models, weigh the effect sizes of individual datasets based on their respective sample size (although Bayesian models for meta-analysis also exist, Röver (2017)), this systematic bias can easily carry over to the meta-analytic findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the follow up response rate in the present study was relatively high at 81%. Thus, any potential variability can be predominantly due to recall bias of the respondents, which has been reported as substantial for unrepresentative surveys [17]. However, the phone survey used as follow up in the present study was performed by quali ed study personnel, and the participants were highly likely to answer the follow up questions accurately due to potential relevance of these questions to the parental microcirculation study.…”
Section: Limitationsmentioning
confidence: 98%
“…No: 'big' does not equate to 'quality'; a large, unrepresentative sample will provide poorer inferences about a population than a small, highly representative sample. An attempt to test this has been made by Bradley et al 4 through defining a formal measure that links data quantity, quality and problem difficulty, applied to Covid vaccine uptake in US adults. They compared a well-designed household survey of around 1000 people per week, to two much larger opportunistic surveys from Delphi-Facebook (250 000 people per week) and Census Household Pulse (75 000 people every 2 weeks).…”
mentioning
confidence: 99%